Natural Deep Eutectic Solvents as Alternative Flavonoid Extractants from the Sedative Plant Composition - M. A. Dzhavakhyan; Yu. E. Prozhogina; O. K. Pavelieva; E. I. Kalenikova (Разработка и регистрация лекарственных средств, 2022)
Introduction. Natural deep eutectic solvents (DESs) are promising extractants for many biologically active substances from plant raw materials. They are biodegradable, safe, stable, their production is affordable and easily feasible, and the extraction efficiency is comparable to known organic solvents. In this regard, interest in deep eutectic solvents has been steadily growing in recent years, and they are being used in various fields of chemistry, pharmaceuticals and the food industry.Aim. The purpose of this work was to study the possibility of extracting flavonoids from plant raw materials using deep eutectic solvents, as well as to compare the efficiency of their extraction with traditional solvents.Materials and methods. The extraction of flavonoids was carried out from the collection of a plant composition consisting of the herb of motherwort cordial (common motherwort) (Leonurus cardiaca L.), the herb of St. John's wort (Hypericum perforatum L.), the herb of lemon balm (Melissa officinalis L.) and the herb of creeping thyme (thyme) (Thymus serpyllum L.) in a ratio of 4 : 2.5 : 2.5 : 1, crushed to a particle size of 2–3 mm. 21 eutectic solvents based on betaine hydrochloride and choline bitartrate as hydrogen bond acceptors were used as extractants.Results and discussion. The extracting ability of 21 experimental compositions of DESs was studied. The influence of the water content in the composition of DES, as well as the effect of temperature on the extraction process, has been studied. Quantitative determination of flavonoids in terms of rutin was carried out by differential spectrophotometry at a wavelength of 410 ± 2 nm. The maximum yield of flavonoids was achieved using a 40 % aqueous solution of DES based on betaine hydrochloride and propylene glycol in a molar ratio of 1 : 3 at 60 °C.Conclusion. The recovery ability of the obtained DES is comparable in efficiency and even slightly exceeds that of the classic extractant for the investigated composition – 70 % ethyl alcohol. Further development and optimization of the process of using DESs is a promising direction for the development of chemistry and pharmaceutical technology.